UNDERSTANDING THE IMPORTANCE OF THE CONCEPT OF THE CONSUMER BEHAVIOR - AMRESHWAR KUMAR SHRIVASTAVA (International Journal of Multidisciplinary Research and Studies, 2020)
Consumer patterns reveal aspirations. It shows who buys, why, and how. This evidence is convincing. The findings illuminated customers' thinking and their adaptation to new situations. Urban consumer purchasing habits changed due to major population movements and disposable income increases. Due to increased competition and variety, marketers have been able to better understand the many factors that affect hosiery product demand. This study examines why people buy hosiery. Families, societies, cultures, and locations influence consumers, but their personalities, perceptions, and motivations determine their choices. This process has three phases: before the purchase, during the buying decision, and after the purchase. Income, social status, education, and brand loyalty can influence buying decisions. Price, packaging, perceived value, cost-benefit analysis, alternative brands, and more might influence a purchase. Marketers must utilise advertising to build brand awareness and consumer relationships because it lasts. Brand loyalty occurs when a buyer buys the same brand after the label is changed, indicating changing purchase habits. India's retail industry has boomed in recent decades. India has traditional and nontraditional retailing. Organized retailing formats have helped the company grow. Retail business practises are changing. India's retail sector is booming, driving storefront demand. India's retail consumer culture is also fueled by debit and credit card use. Consumer power, intellect, and retail savvy are driving retail shopping behavior research. Customers assess a store before buying.